Assessing the impact of the country’s economic security on export development in the agro-industrial sector - E. V. Nagovitsyna; E. A. Bratukhina (Вестник университета)
While the conditions of the world markets functioning factors change, it is required the development of a new effective strategy for food security in the Russian Federation. The global economic shock caused by the COVID-19 pandemic, changes in the structure and volume of world trade, and political crises in a number of EAEU member states also force us to pay special attention to food security. The relevance of this research is due to: 1) the processes of globalisation and integration of national markets, which is why new foreign economic and foreign trade relations are increasingly being formed; 2) the crisis of the coronavirus pandemic, which is why many foreign trade processes in Russia and a number of other countries are disrupted; 3) the commodity groups under consideration, the uncontrolled volume of exports of which can cause a food threat to the country. The purpose of the study is to analyse the problems of assessing food security within the country in the implementation of foreign economic activity and the supply of agro-industrial complex goods to foreign markets. The objectives of the study are to identify ways to assess food security. Measurement tools are proposed that help to assess food security at the national level, assess household access to food and its purchase, and also allow measuring food consumption and use. To date, the solution of this problem is one of the main tasks, both within individual regions and the country as a whole.